Der parteiliche Journalist : die Geschichte des Radio-Features in der DDR - Conley, Patrick 1965- (Metropol, 2012)
The Funkhaus Nalepastrasse, the broadcasting studio in East Berlin, was a world apart. Five radio programs were broadcast all over the German Democratic Republic (GDR) from this central location. Radio documentaries, called features, were a permanent part of the program. Now for the first time, the numerous sound recordings, scripts, and papers of the GDR feature are evaluated in this book. In addition, 40 eyewitnesses have been interviewed about their work on the cultural programs: authors, dramaturges, and producers talk about their "radio niche". The book conveys a precise insight into the conditions of journalism and art in the "real existing socialism